2014
DOI: 10.1590/2237-6089-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior during the first 24 hours of psychiatric admission

Abstract: Objective: To investigate the association between aggression in the first 24 hours after admission and severity of psychopathology in psychiatric inpatients. Methods: This cross-sectional study included psychiatric patients admitted to Hospital Universitário de Santa Maria, in Santa Maria, southern Brazil, from August 2012 to January 2013. At their arrival at the hospital, patients were interviewed to fill in the Brief Psychiatric Rating Scale (BPRS) form, and any aggressive episodes in the first 24 hours afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
1
5
0
3
Order By: Relevance
“…Our results are in line with the existing evidence indicating a higher risk of aggressions during the first days of hospitalization as we found that almost 29.8% of the reports regarded the 5 days after admission (Barlow et al, 2000; Calegaro et al, 2014) and 35.1% after 20 days. A high percentage of incidents in the first 5 days might be explained by partial ineffectiveness of pharmacotherapy as well as that the acute psychiatric symptoms that lead to the hospitalization.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with the existing evidence indicating a higher risk of aggressions during the first days of hospitalization as we found that almost 29.8% of the reports regarded the 5 days after admission (Barlow et al, 2000; Calegaro et al, 2014) and 35.1% after 20 days. A high percentage of incidents in the first 5 days might be explained by partial ineffectiveness of pharmacotherapy as well as that the acute psychiatric symptoms that lead to the hospitalization.…”
Section: Discussionsupporting
confidence: 93%
“…In the first 24 hours or first week, the highest percentages of aggression were measured [53,72,79,81]. Only a minor proportion of the admitted patients were involved in the majority of incidents [51, 54, 56, 62, 72, 78, 85-88, 90, 93].…”
Section: Plos Onementioning
confidence: 99%
“…In 12 papers diagnosis had no significant contribution to the development of aggression [50,53,60,70,75,77,78,88,90,92,99,101].…”
Section: Patient Factors Associated To Aggressionmentioning
confidence: 99%
“…Hostility has been conceptualized by anger/aggression scholars as an enduring attitudinal disposition toward anger and aggressive behavior (e.g., Berkowitz, 1993; Buss, 1961; Novaco, 1994). Like traditional anger disposition measures, BPRS Hostility has been found to be associated with inpatient aggression incidents (e.g., Amore et al, 2008; Carr et al, 2019; McNiel & Binder, 1994; Calegaro et al, 2014) and with inpatient anger measures, as well as violence (Doyle & Dolan, 2006a). It has very good inter‐rater reliability, with r = 0.86 for a clinical sample (Overall & Gorham, 1962).…”
Section: Methodsmentioning
confidence: 99%
“…Hostility has been found to be associated with inpatient aggression incidents (e.g., Amore et al, 2008;Carr et al, 2019;McNiel & Binder, 1994 ;Calegaro et al, 2014) and with inpatient anger measures, as well as violence (Doyle & Dolan, 2006a). It has very good inter-rater reliability, with r = 0.86 for a clinical sample (Overall & Gorham, 1962).…”
mentioning
confidence: 99%